Climate change and abiotic stress mechanisms in plants. Issue 2 (30th April 2019) - Ferguson, John N.
Abstract: Predicted global climatic change will perturb the productivity of our most valuable crops as well as detrimentally impact ecological fitness. The most important aspects of climate change with respect to these effects relate to water availability and heat stress. Over multiple decades, the plant research community has amassed a highly comprehensive understanding of the physiological mechanisms that facilitate the maintenance of productivity in response to drought, flooding, and heat stress. Consequently, the foundations necessary to begin the development of elite crop varieties that are primed for climate change are in place. To meet the food and fuel security concerns of a growing population, it is vital that biotechnological and breeding efforts to harness these mechanisms are accelerated in the coming decade. Despite this, those concerned with crop improvement must approach such efforts with caution and ensure that potentially harnessed mechanisms are viable under the context of a dynamically changing environment.